2021
DOI: 10.1002/cjoc.202000660
|View full text |Cite
|
Sign up to set email alerts
|

Cu‐Catalyzed Cascade Cyclization of Ketoxime Acetates and Alkynals Enabling Synthesis of Acylpyrroles

Abstract: Copper catalysis | Nitrogen heterocycles | Cyclization | Ketoximes | AlkynalsA facile copper-based catalytic system has been developed to enable efficient cyclization of methylketoximes and alkynals. This protocol provides a viable entry to synthetically and pharmaceutically useful 2-acylpyrroles with a broad range of compatible functionalities. Mechanistically, a key acyl migration is probably involved that leads to the formation of N-acyl pyrroles or otherwise NH pyrroles by further hydrolysis. More importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…As shown in Scheme 27 , firstly, isocyanide 20a was deprotonated by DBU to form A. Nucleophilic attack A to 1a generated the intermediate B that underwent further attack by the second molecule 20a to afford C. Next, deprotonation of C followed by intra-molecular cyclization produced E. Removal of HCN created intermediate F, which upon interconversion furnished the target product 20b. Meantime, another procedure for the synthesis of acylpyrrole derivatives through the cyclization of ketoxime acetates and alkynyl aldehydes was performed by Huang et al 38 The reaction moved upon using 15 mol% of CuBr as the inexpensive metal catalyst to promote synthesizing 2,5-disubstituted and 1,2,5-trisubstituted pyrroles. Both electron-rich and electron-deficient aromatic rings were tolerated under these conditions and gave desired products in moderate yields.…”
Section: Synthesis Of N-heterocyclic Compoundsmentioning
confidence: 99%
“…As shown in Scheme 27 , firstly, isocyanide 20a was deprotonated by DBU to form A. Nucleophilic attack A to 1a generated the intermediate B that underwent further attack by the second molecule 20a to afford C. Next, deprotonation of C followed by intra-molecular cyclization produced E. Removal of HCN created intermediate F, which upon interconversion furnished the target product 20b. Meantime, another procedure for the synthesis of acylpyrrole derivatives through the cyclization of ketoxime acetates and alkynyl aldehydes was performed by Huang et al 38 The reaction moved upon using 15 mol% of CuBr as the inexpensive metal catalyst to promote synthesizing 2,5-disubstituted and 1,2,5-trisubstituted pyrroles. Both electron-rich and electron-deficient aromatic rings were tolerated under these conditions and gave desired products in moderate yields.…”
Section: Synthesis Of N-heterocyclic Compoundsmentioning
confidence: 99%
“…Recently, oxime esters, which are stable and easy to prepare, have been used as versatile building blocks in the chemical industry and academia. 6 In this context, significant progress has been made in the development of transition-metal catalyzed or metal-free protocols of oxime esters, especially for the synthesis of five-membered N-heterocycles, such as pyrroles, 7 pyrazoles, 8 oxazoles, 9 isoxazole, 10 thiazoles, 11 imidazoles, 12 and triazoles 13 (Scheme 1, top). Notably, oxime esters proved to be N–C–C or N–C synthons in the above reactions by the cleavage of the N–O bond.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12] In this context, several research groups have reported the use of oxime acetates for the construction of substituted pyridines. [13][14] For instance, Guan and co-workers reported transition metal catalysed synthesis of substituted pyridines via the condensation of oxime acetates with one carbon source such as aldehydes, dimethyl anilines and dimethyl formamides. [15][16] Recently, our group have also developed an efficient access to triaryl substituted pyridines using phenyl acetic acids as C1 source (Scheme 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Among these protocols, the strategies that utilized ketoxime acetates as one of the substrates have been enchanting because of the versatility of oxime acetates, having ability to undergo reductive N−O bond cleavage and/or to serve as a directing group for C−H activation [11–12] . In this context, several research groups have reported the use of oxime acetates for the construction of substituted pyridines [13–14] . For instance, Guan and co‐workers reported transition metal catalysed synthesis of substituted pyridines via the condensation of oxime acetates with one carbon source such as aldehydes, dimethyl anilines and dimethyl formamides [15–16] .…”
Section: Introductionmentioning
confidence: 99%